Offshoring and the polarisation of the demand for capital - Dirk Bursian; Arne J. Nagengast (Deutsche Bundesbank, 2018)
While there is a consensus in the literature that offshoring has a polarising effect on the skill structure of labour demand, little is known about its impact on the capital side. In this paper, we analyse the effect of offshoring on the demand for capital by asset class using a rich country-sector panel dataset. Estimating a system of factor demand equations, we document that offshoring reduces the relative demand for non-ICT capital, thereby also polarising the demand for capital. Our results are robust against a wide range of specifications and methodological choices including an IV approach to address endogeneity concerns.
Keywords: F14; F62; F20; E22; 330; offshoring; trade; global value chains; demand for capital; user costs of capital; ICT